Regulasi Pemanfaatan Lahan Gambut Dalam Tinjauan Economic Analysis of Law dan Pendekatan Konservasi - Maya Simorangkir (Justice Legislation and Crime Journal, 2025)
Government Regulation No. 57 of 2016 on Amendment to Government Regulation No. 71 of 2014 on protection and management of peat ecosystems that substantively emphasizes on sustainable management of peat so there must be a balance of conservation function and aquaculture function, especially on peatlands already already opened and cultivated. Indonesian Peatlands Data that problems related to social and economic aspects will be experienced by many forestry and oil palm business actors including peasants who use peatlands because according to Article 23 paragraph (3) peatlands declared damaged if the groundwater surface in peatland 0.4 meters below the surface of the peat or exposure to pyrite sediments. Currently land for acacia and palm oil plants requires groundwater levels between 0.6-0.8 meters below the surface of the peat. Furthermore, with advances in current technology, the exposure of pyrite sediments can still be used for acacia plants and oil palm. The PP indicates the inconsistency of our peat regulation due to some previous legal products, namely: (i) of the 1945 Constitution of the State of the Republic of Indonesia Article 33 paragraph 3 which states that: "Earth and water and natural resources stumbled in it is controlled by the State and used for the greatest prosperity of the people "; (ii) of Law No.32 of 2009 on Environmental Protection and Management in accordance with the provisions of Article 21 paragraph (3) letter f and paragraph 5, that in order to determine the occurrence of environmental damage, there shall be provisions of the defect criteria, including: standard criteria for ecosystem damage (one of which is the peat ecosystem) and standard criteria for damage due to climate change, (iii) the Importance of Peat Ecosystem Protection and Management.